(untitled) (Research, Society and Development, 2025)
This study aimed to analyze scientific evidence on the self-efficacy of Nursing and Medical students, considering its relationship with sociodemographic profile, health conditions, and academic performance. An integrative literature review was conducted based on the methodological framework of Souza, Silva, and Carvalho, using the PICO strategy to develop the guiding research question. Searches were performed in LILACS/BVS, PubMed, and SciELO with no time restriction, allowing a comprehensive understanding of the conceptual evolution of self-efficacy. Studies in Portuguese, English, and Spanish available in full and directly related to the topic were included. Of the 78 articles initially identified, 9 met the eligibility criteria and were included in the final sample. Results showed that self-efficacy is consistently associated with academic performance, mental health, learning strategies, resilience, and student engagement. Active learning methodologies, emotional support from instructors, practical experiences, and intrinsic motivation significantly contributed to higher self-efficacy levels. Conversely, stress, burnout, and low perceived competence were linked to poorer performance. It is concluded that self-efficacy plays a central role in Nursing and Medical education, influencing both academic achievement and emotional well-being. Strengthening self-efficacy should be incorporated into pedagogical practices as a key strategy to promote learning, resilience, and preparedness for clinical practice.